Strengthening the character of the love of the motherland through the of the Nyello 'Aeng dance at the Sanggar Bimbingan Jalan Kebun Selangor Malaysia - Sulalah, Anis; Kuswandi, Iwan; Misbahudholam AR, Muhammad (Electronic Journal of Education, Social Economics and Technology, 2024)
Character education is an effort made by educators to form good character in students. It includes creativity, feeling, and intention so that it can be applied in everyday life and can be helpful in the surrounding environment. The character of love for the homeland is an attitude that reflects a sense of pride in the Indonesian nation. For that, the character of the ideals of the motherland needs to be instilled in every citizen. The background of this study is the lack of knowledge of students of the Jalan Kebun Guidance Studio about Indonesia because students of the Jalan Kebun Guidance Studio are children of illegal immigrant workers from Indonesia who live and grow up in a neighbouring country. This study aims to introduce traditional dance to strengthen the character of love for the homeland in SB Jalan Kebun, Selangor, Malaysia. This study uses a qualitative approach with a descriptive case study research type. This study uses data collection through interviews, observations, and documentation. The study results showed that students were enthusiastic, experienced, and excited about learning the Nyello' Aeng dance, which contains the value of the love for the homeland.